Topography difference as an indicator of groundwater catchment and its importance for tourism development in the municipality of the Western Mountain using geographic information systems (Journal of Libya for geographical studies, 2024)
This study seeks to analyze the relationship between the places of groundwater gathering based on the terrain difference, and the positive effects that can be achieved by tourism in the municipality of the Western Mountains, the study relied on the use of terrain difference as an indicator to assess the possibility of groundwater collection, which is one of the applications of spatial analysis, geographic information systems, and to derive the information allocated to the study, the digital elevation model DEM was used. digital elevation model obtained from the US Geological Survey website and the work of Mosictif were used for fifteen satellite visualizations, the approved layers were prepared, and equations were applied to produce a map of groundwater collection sites, and the Esri site was relied on to obtain satellite visuals of the sentinel 2 satellite with a resolution of 10 meters for the year 2022 to clarify the land cover and use the Ministry of Tourism to determine tourist sites.  The study showed that the most likely areas for the presence of groundwater are at the southwestern tip west of Qurayyat and south of Jado, which are the promising areas for tourism development, and it was found that the height of 400, 500 and 600 meters is more enjoying the picturesque landscape because of the presence of 81.25% of the natural water springs in it, and it has 90.6% of the tourist sites, in addition to a rich cultural that contributes to the creation of a diverse and integrated tourism product, as it turned out that all groundwater collection sites are barren lands and pastures, which are suitable for tourist activities such as festivals and riding. Horses, camping and safari trips. The municipality of the Western Mountain has a diverse and integrated tourism product that carries the element of spatial sequencing, which can be used as an important and enjoyable path linking Tripoli and Ghadames, where the water catchment sites are located to the west. The study recommended instead of joint efforts between the Water Authority and the Ministry of Tourism in facing the future water needs of tourism projects and designing smart phone applications that provide information on tourist routes, water gathering places and wells. Conducting research and studies complementary to this study whose objective is to know the quality and level of groundwater in the places where water collects This study identified the provision of support to promising centers and provide them with small plants for purification and treatment of salt water and to improve the quality of drinking water and the development of the necessary programs for their development tourism and publicity.
Keywords: Tourism Development; Mountain Tourism; Water Catchment Index; Terrain Difference; Land Cover; Groundwater; Wells; Laayoune; Spatial Analysis